The perceived role of ward-based primary healthcare outreach teams in rural KwaZulu-Natal, South Africa - Landiwe S. Khuzwayo; Mosa Moshabela (AOSIS, 2017)
Background: The aim of ward-based outreach teams (WBOTs) is to improve access to primary healthcare (PHC) services including health promotion and disease prevention in South Africa. Limited information is available in South Africa on user perceptions of services provided by WBOTs in rural households. Aim: The study aimed to explore community awareness and perception of WBOTs, as well people's motivation to engage and use WBOT services. Setting: The study was conducted between July and September 2015 in iLembe district, KwaZulu-Natal. Methods: This was exploratory-descriptive qualitative research. Purposive sampling technique was used in this study. A total of 16 key informant interviews and 4 focus group discussions were conducted. The voice recordings were transcribed in isiZulu and translated into English. Results: Four themes emerged from the data analysis, namely bringing services closer, organising services, expanding services and forming bridges. Respondents demonstrated insightful knowledge and understanding of services provided by WBOTs. They expressed an appreciation of the way WBOT services brought healthcare closer to people and serve to bridge the gap between the community and local healthcare facilities. Respondents identified unclear WBOT work schedules and the failure to carry medication other than vitamin A as the main challenges. However, WBOTs did deliver medication for controlled chronic patients in their households. Conclusion: The study suggests that WBOTs provide a commendable service, but need to expand their service package to further increase access to PHC services and cater for community health needs.